Democratic Republic of Sao Tome and Principe : Second Review under the Extended Credit Facility, and Request for Waivers for Nonobservance of Performance Criterion and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Sao Tome and Principe's Second Review Under the Extended Credit Facility (ECF) and Request for Waivers for Nonobservance of Performance Criteria and modification of performance criteria. The economic outlook for 2017 and the medium term is favorable, but not without risks. The main sources of short-term risks to the outlook are ongoing pressure on foreign exchange supply, liquidation of Bank Equador, and continued weakness in the banking sector. In addition, the economy will remain vulnerable to global developments, including weak demand in the key European and emerging markets. The IMF staff recommends completion of the second review and the disbursement of an amount equivalent to SDR 634,285 under the ECF arrangement.